Fiber scale numerical investigations on water droplet dynamics on gas diffusion layers. (11th October 2021) - Feng, Pengfei; Tan, Ligang; Cao, Yucheng; Chen, Ding
Abstract: The dynamics of water droplets on fiber layers are investigated by fiber-scale simulation using volume of fluid (VOF) method. The effects of fiber spaces, contact angles at fibers and numbers of layers on droplet dynamics are investigated. Force analysis for the pinned and moving droplets on fiber layers shows that the resistant forces from the wetted fibers at the edge positions rather than middle positions are the dominant force to control the droplet mobility. Force analysis for droplets on the dual-layers fiber layer are also conducted. The results show that the second layer contributes little to hinder the droplet directly due to the insignificant resistant force they provided. However, the second fiber layer enhances the total resistant force from the first layer. Furthermore a simplified model is used to compare with the fiber model. The results indicate that the simplified model can also be used to predict the droplet mobility once the contact angle is given. Graphical abstract: Image 1 Highlights: Fiber scale numerical modeling of droplets on fiber layers is conducted. Resistant forces from the fibers at the edge positions are the dominant forces. The total resistant forces from the first layer dominate the droplet motion. Simplified model neglected fiber structure is compared with the fiber model.